2011
DOI: 10.1039/c1dt10104h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and DFT studies of thione and selone Cu(i) complexes with variable coordination geometries

Abstract: Coordination of Cu(I) halides with N,N'-dimethylimidazole selone (dmise) and thione (dmit) ligands was examined by treating CuX (X = Cl, Br, I) with one or two equivalents of dmise or dmit. The reaction of CuI and CuBr with one molar equivalent of dmise results in unusual selenium-bridged tetrameric Cu(4)(μ-dmise)(4)(μ-X)(2)X(2) copper complexes with average Cu-Se bond lengths of 2.42 Å and a Cu(2)(μ-X)(2) core (X = I (1) or Br (6)) that's in a rhomboidal structure. The reaction of CuX (X = Cl, Br, and I) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 79 publications
3
50
0
Order By: Relevance
“…27,28 Notably, the Cu(II/I) reduction potential of the dinuclear copper chalcogenone complexes 1 to 10 can be tuned in a 470 mV window from 102 mV to -369 mV by simply changing the nature of the chalcogen donor and the denticity of thione and selone ligands. The reduction potentials from the bidentate chalcogenones indicate that increasing the length of the linker from methylene to ethylene results in more negative reduction potentials.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 Notably, the Cu(II/I) reduction potential of the dinuclear copper chalcogenone complexes 1 to 10 can be tuned in a 470 mV window from 102 mV to -369 mV by simply changing the nature of the chalcogen donor and the denticity of thione and selone ligands. The reduction potentials from the bidentate chalcogenones indicate that increasing the length of the linker from methylene to ethylene results in more negative reduction potentials.…”
Section: Resultsmentioning
confidence: 99%
“…us, the Cu(II)(OSe) 2 /Cu(I)(OSeH) 3 + and Cu(II)(ESe) 2 /Cu(I)(E-SeH) 3 + redox couples are 0.17 V and 0.15 V more reducing than their respective sulfur analogues. While the sulfur compounds have the more positive potential and therefore suggests a greater protection from the recycling of Cu(I) to Cu(II) from past experiments into the binding of N,N′dimethylimidazole selone and N,N′-dimethylimidazole thione to Cu, similar differences in reduction potentials were observed [36,40]. In particular, the reduction potentials for the Cu(II)-selone complexes were more negative than the Cu(II)-thione analogues by an average of 0.11 V [36,40].…”
Section: Resultsmentioning
confidence: 68%
“…Initial geometries of the Cu-Se complexes were modeled from previous computational studies [6] on ESH and OSH binding to copper where trigonal-planar and square-planar geometries were assumed for the Cu(I) and Cu(II) complexes, respectively. It is noted that experimental work has shown that for Cu(I)-Se containing complexes, a three-coordinate trigonal planar coordination geometry around the Cu center exists [35,40]. For the Cu(II) complexes, the cis and trans conformations involving OSeH and ESeH were investigated; moreover, for the ESeH-Cu(II) complexes, the binding of ESeH via either the δ-or ε-nitrogen to the copper was investigated.…”
Section: Methodsmentioning
confidence: 99%
“…The title compound shows the same trans configuration as the bis-N,N′-dimethylimidazole-thione-Cu(I) compound (Kimani et al, 2011) or bis-N,N′-dimethylimidazolidine-thione-CuCl (Devillanova et al, 1980) whereas the cis configuration is also known for bis-N,N′-dimethylimidazole-thione-CuX (X = Cl, Br, I) (Kimani et al, 2011). In contrast to all the reported complexes in the title compound both Cu and Cl atoms lie on general positions and the two Cu-S bond lengths differ strongly with Cu-S1 2.2662 (10) and Cu-S2 2.2270 (10) Å.…”
Section: S1 Commentmentioning
confidence: 95%
“…For structures of related Cu complexes, see: Devillanova et al (1980); Kimani et al (2011). For background to effective antioxidants, see: Bhabak et al (2010); Yamashita & Yamashita (2010).…”
Section: Related Literaturementioning
confidence: 99%